ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN RUMAH DI PERUMAHAN GREEN HILLS REGENCY TRENGGALEK (Studi Pada PT. Rimbun Perusahaan Developer Cabang Trenggalek) - Hendrawaty, Rina; Pribadi, Nukhan Wicaksana (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
The purpose of this study was to determine the influence of any proceduresthat affect consumer decision in purchasing the home , either partially orsimultaneously between the marketing mix consisting of price , product , promotion ,and the location of the consumer's decision to purchase the house at PT. Rimbunespecially leafy Green Hills Regency Trenggalek housing residents. Methods ofstatistical analysis used multiple linear regression analysis . Results of this researchindicate that the dimension of the tax procedure consists of price , product , promotionand location simultaneously significantly influence consumer decision in purchasing aresidential home in Green Hills Regency Trenggalek. While partially dimensions ofprice , product , promotion and location have a significant influence on consumerdecisions in the purchase of a residential home in Green Hills Regency Trenggalek.Keywords : Price , Product , Promotion , location , and Consumer Decision .